Qualidade do guacamole elaborado com abacate ‘fuerte’ submetido a hidrotermia - Daiuto, Érica Regina [UNESP]; Russo, Viviane Citadini [UNESP]; Vieites, Rogério Lopes [UNESP]; Fumes, Joana Giffoni Figueiredo [UNESP]; Cábia, Nathalie Cardoso [UNESP] (My University, 2011)
The aim of this work was to evaluate the guacamole quality and acceptability conserved by the cold and elaborated with 'fuerte' avocados submitted to thermal treatment. The fruits recently picked were submitted to bath water to 45 ºC for 5, 10, 15 and 20 minutes, stored under refrigeration (10 ± 1 ºC and 90±5% of UR) and evaluated for 15 days as the polyphenol oxidase activity (PPO). Ripened pulp was characterized as for the pH, acidity titrable and color. After this experiment, ripened fruits were submitted to bath water at 45ºC for 15 minutes and to follow the guacamole was elaborated the guacamole. The product was conditioned in polyethylene+nylon packages and submitted to refrigeration, being the evaluations to the 0, 3 and 7 days of storage. The product was also submitted to freezing to -18ºC, where they stayed stored, being the evaluations to the 0, 30, 60 and 90 days. After the 90 days under these conditions the product was maintained under refrigeration and evaluated during 7 days. The analyses in the guacamole were the same of the pulp, being also madelipids content. Guacamole elaborated with fruits submitted to the thermal treatment presented atthe end of the storage the smallest value of titratable acidity and larger lipids content in relation tocontrol. The thermal treatment was effective in the reduction of the enzymatic activity; however,larger darkening index was verified in the samples submitted to this treatment. The treatment didn'taffect the sensorial product quality in relation to sample control.

O objetivo desta pesquisa foi avaliar a qualidade e aceitabilidade do guacamole conservado pelo frioe elaborado com abacates ‘fuerte’ submetidos a hidrotermia. Os frutos recém colhidos foramsubmetidos a banho-maria a 45 ºC por 5, 10, 15 e 20 minutos, armazenados sob refrigeração (10 ± 1ºC e 90±5% de UR) sendo avaliados durante 15 dias quanto a atividade da polifenoloxidase (PPO). Apolpa amadurecida foi caracterizada quanto ao pH, acidez titulável e cor. Após este ensaio os frutos,amadurecidos foram submetidos a banho-maria à 45ºC por 15 minutos e a seguir foi elaborado oguacamole. O produto foi acondicionado em embalagens de nylon+polietileno e submetido àrefrigeração, sendo as avaliações aos 0, 3 e 7 dias de armazenamento. O produto também foicongelado emfreezer’doméstico a -18ºC, onde permaneceu armazenado, sendo as avaliações aos 0, 30, 60 e 90 dias. Após os 90 dias sob estas condições o produto foi mantido sob refrigeração e avaliado aos 7 dias. As análises no guacamole foram as mesmas da polpa, sendo feita também análise do teor de lipídeos. O guacamole elaborado com frutos submetidos a hidrotermia apresentaram ao final do armazenamento o menor valor de acidez titulável e maior teor de lipídeos em relação a testemunha. O tratamento térmico foi efetivo na redução da atividade enzimática, no entanto, constatou-se maior índice de escurecimento nas amostras submetidas a este tratamento. Os tratamento não afetou a qualidade sensorial do produto em relação a amostra testemunha.
Quality of guacamole elaborated with ‘fuerte’ avocado submitted to thermal treatment
Keywords: Persea americana Mill.; Processing; Fresh cut; Persea americana Mill.; Processamento; Minimamente processado